Field and laboratory selection of brassicaceous plants that differentially affect infestation levels by Delia radicum. (8th December 2014) - Kergunteuil, A.; Cortesero, A. M.; Chaminade, V.; Dourlot, S.; Paty, C.; Le Ralec, A.; Dugravot, S.
Abstract Several plant traits control plant–insect interactions and shape host range of herbivorous insects according to their degree of dietary specialization. Understanding how plant species diversity influences herbivore infestations is of interest for the development of alternative crop protection strategies. In a pest management context, an appropriate selection of plants can modify pest distribution at the field scale. To develop a 'push–pull' strategy against the cabbage root fly, Delia radicum, we conducted a field study to both determine which plants exhibit contrasted pest infestation levels and to evaluate their influence on egg predation activity. Our field experiment reveals that infestation levels of brassicaceous plants by the cabbage root fly in the field can vary considerably according to plant genotype and species, while the number of predated eggs is only slightly affected by plant species. Olfactometry studies carried out under laboratory conditions revealed that plants harbouring the highest number of eggs in the field were also highly attractive, suggesting that olfactory stimuli are responsible, at least partially, for the differential infestation levels observed in the field. In a 'push–pull' context, this study demonstrates that different brassicaceous plants could be used to redistribute cabbage root flies in broccoli crops without compromising herbivore control by natural enemies. In addition, the importance of plant volatiles for infestation levels suggests a potential for developing a semiochemically assisted 'push–pull' system in which trap plants would be enhanced by synthetic release of attractive compounds.